Há diferenças que fazem diferença? Lutas identitárias e conflitos ambientais nas dinâmicas de expansão capitalista da Amazônia - Wendell Ficher Teixeira Assis (Universidade do Vale do Rio dos Sinos (UNISINOS), 2015)
In a context of territorial disputes, the politicization of identity has represented a way of supporting the peasant populations and traditional communities to stay in their place. The culture as a resource and the resource to the culture has been use as strategies of mobilization to obstruct the dynamics of expropriation that affect these population in so far as the economical fronts advance on the new territories. To try to account for this tangle universe that plasma at the junction between culture, territorial fights, socio-legal recognition and environmental preservation, the article is anchored in fields works conducted in the western region of Pará, which over the last decade has been locus of intense conflicts of lands involving new areas of capitalist accumulation and traditional populations, indigenous and peasant populations. From the data collected in the works fields, it will aim to demonstrate how the use of culture in association with the politicization of differences has been tacked by territorial belonging to guarantee the permanence of traditional people in their ancestral places occupied. Then, the article analyzes the decision of the Supreme Court in the judicial case which challenges the continuous demarcation of the Raposa Serra do Sol. This case is paradigmatic to understand the speeches and arguments delivered by the Brazilian main Court regarding the recognition of cultural and territorial rights. The data and analysis collated here, it will aim to demonstrate how the use of culture in association with the politicization of the differences has been brought to guarantee the permanence of traditional people in their ancestral places. Nevertheless, the judiciary, when faced with universalizing categories, as a nation, territory and sovereignty, has operated a particularization of the rights of traditional communities, turning them into a kind of public interest in the second category.